2005
DOI: 10.1055/s-2005-864098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Effects of Several Isothiocyanates onHelicobacter pylori

Abstract: The antibacterial activity of sulforaphane [4-(methylsulfinyl)butyl isothiocyanate] has been previously described. We have analysed the activities of 12 isothiocyanates (ITC) including sulphoraphane on 25 strains of Helicobacter pylori using an agar dilution assay. In addition, bactericidal effects against H. pylori were determined for the 6 most active ITCs, both directly and against intracellular bacteria in cultured human epithelial (HEp-2) cells. The MIC90 values for these ITCs ranged between 4 and 32 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 17 publications
4
60
0
1
Order By: Relevance
“…These compounds also have the potential to control agricultural and public health insect pests (Tsao et al, 1996). For example, Helicobacter pylori bacterium was found to be highly susceptible to 4-(a-L-rhamnopyranosyloxy) benzyl isothiocyanate and various other isothiocyanates, which are degraded products of glucosinolates Haristoy et al, 2005). H. pylori is a major cause of gastric and duodenal ulcers, and is a major risk factor for gastric cancer.…”
Section: Plants Containing Multibioactive Compoundsmentioning
confidence: 99%
“…These compounds also have the potential to control agricultural and public health insect pests (Tsao et al, 1996). For example, Helicobacter pylori bacterium was found to be highly susceptible to 4-(a-L-rhamnopyranosyloxy) benzyl isothiocyanate and various other isothiocyanates, which are degraded products of glucosinolates Haristoy et al, 2005). H. pylori is a major cause of gastric and duodenal ulcers, and is a major risk factor for gastric cancer.…”
Section: Plants Containing Multibioactive Compoundsmentioning
confidence: 99%
“…It is also a selective and highly potent antimicrobial agent against H. pylori in vitro and it prevents development of chemically induced stomach tumors in a rodent model (11). Several studies have confirmed the anti-H. pylori activity of sulforaphane (12,13), and an early attempt to evaluate its efficacy in vivo with only one biomarker of efficacy has identified some of the issues that would be likely to occur in a trial in which complete eradication of H. pylori is not required as an end point (14). A subsequent pilot study in Detroit reported eradication of infection in three of nine H. pylori-infected patients (15).…”
mentioning
confidence: 93%
“…Sulforaphane is a plant secondary metabolite that is synthesized from glucosinolates after damage to the plant, presumably to protect from microbial infestation. It has demonstrated antimicrobial efficacy against Helicobacter pylori (13,16,17) and in another study 23 of 28 tested microbes (25). The chemical is therefore likely exhibiting a hormesis effect by inducing Nrf2 (43).…”
Section: Modulating the Nrf2 Pathwaymentioning
confidence: 99%